The Utilization of LiCSBAS for Deformation Monitoring in Geresa Segment of Matano Fault, Central Sulawesi, Indonesia - Muhammad Razzaaq Al Ghiffari; Djoko Nugroho; Rachmat Ramadhan; Mochamad Rifat Noor; Noviarso Wicaksono; Agustan (Journal of Geoscience, Engineering, Environment, and Technology, 2024)
Sulawesi is situated between the confluence of three plates, resulting in a very complex tectonic setting on the island. This has an impact on the occurrence of geological structures, including faults. One of them is the Matano Fault which consists of 6 segments (Kuleana Segment, Pewusai Segment, Matano Segment, Pamsoa Segment, Ballawai Segment, and Geresa Segment). The research area is located in Morowali Regency, covering the Geresa Segment. Morowali Regency recorded an earthquake with a magnitude of 5.7 in 2012. This indicates that deformation has occurred. Therefore, this study aims to identify the deformation velocity around the Geresa Segment area. The methods used are geological observation and satellite image data processing to obtain information on deformation rates. The geological field study includes aspects of geomorphology, geological structure, and the rock types distribution. Meanwhile, the processing of satellite image data in the form of InSAR is carried out through the LiCSBAS package tools that has been integrated with LiCSAR. The analysis results illustrate the difference in deformation velocity around the Geresa Segment area. The area which is composed of Tolaka formation and Ultramafic complex tends to uplift with a deformation rate of up to 17 mm/year. In addition, alluvium that covers the southeastarn part has a land subsidence of up to 7 mm/year.